Physiological Responses of Dogs to Different Housing Systems - Fazio, Esterina; Cravana, Cristina; Giuliano, Antonio; Medica, Pietro (Acta Scientiae Veterinariae, 2019)
Background: The hypothalamic-pituitary-adrenal (HPA) axis undergoes adaptations throughout housing system that might contribute to the avoidance of adverse effects of welfare status in dogs housed in a shelter. Nevertheless, the influence of housing systems and stabling time on glucose and PCV changes is little known. The purpose of the present study was to evaluate the patterns of cortisol, glucose and PCV in dogs housed in a kennel and normal environments, evaluating the differences between housing systems, by taking account the different stabling time and sex. Materials, Methods & Results: The study comprised 98 cross-breed dogs, aged 4 ± 1.5 years, lodged in a kennel (observational group I: N= 61, 29 females and 27 males), in paired household dogs (control group II: N= 25, 13 females and 12 males) and in unpaired household dogs (control group III: N= 12, 6 females and 6 males). Females of both groups were spayed. The subjects were studied on the basis of different stabling times, ranged among <1 year, 2 years and 4 years, and different sex. Discussion: This observational study showed that kennelled males lodged for 2 (P < 0.01) and 4 (P < 0.001) years showed lower cortisol concentrations than males lodged <1 year, males lodged for <1 year (P < 0.001) showed higher cortisol concentrations than females; males lodged for 4 year showed lower cortisol concentrations (P < 0.01) than females. Kennelled females lodged for 4 year showed higher PCV values (P < 0.001) than females lodged for <1 year. Paired and unpaired household females and males lodged for 4 years showed lower cortisol concentrations (P < 0.01) than 2 years and <1 year. Paired and unpaired household females and males lodged for short-, medium- and long-term times showed higher glucose concentrations (P < 0.001) than kennelled dogs. This study showed significant changes of circulating cortisol, glucose and PCV values inter- and intra-groups, according to different housing systems, stabling time and sex. The magnitude of cortisol decreases after 2 and 4 years of stabling time in kennelled male dogs could suggest a stimulus-response relationship, probably due to adaptive responses. Interestingly enough in this observational study was that the exact consummatory event could be represented by the long stabling time itself, observed only in males. Moreover, the significant differences of cortisol concentrations between males and females in group I after a stabling time of <1 and 4 years confirm the wide variability of HPA activity independent of the different sex of dogs. The physiological higher glucose concentrations in household dogs than kennel dogs showed that the normal home environment offers probably more rich stimuli than kennel, independent of stabling times and sex. It is possible to suppose that the housing system of dogs also results in significant rise of organ reserve and adaptability, presumably due at early greatest in functional changes in the catecholaminergic system and related increased hepatic glycogenolysis and gluconeogenesis. Concerning the PCV changes, data obtained confirmed the disagreement among authors about sex differences in the circulating mass of erythrocytes according to different age and sex. In conclusion, this is an observational study on the adaptive responses of circulating cortisol, glucose and PCV patterns to different housing systems in both kennel and household, leading to the question of physiological relevance concerning the effects of different stabling, according to the quality of dogs’ life.